Risk Factors for Infection Associated with Ischemic Stroke in Patients over 60 Years of Age - Alexis Suárez Quesada; Alexis Álvarez Aliaga; Andrés José Quesada Vázquez; Eduardo René Valdés Ramos; Ezequiel Ernesto López Espinosa (Revista Finlay, 2024)
Foundation: infection associated with stroke is the most important medical complication because it increases both the morbidity and the mortality rate in the first 30 days after the event occurs. Objective: to identify risk factors for infection associated with ischemic stroke in patients over 60 years of age. Methods: a prospective cohort analytical study was carried out in patients over 60 years of age with a diagnosis of ischemic stroke treated at the Carlos Manuel de Cespedes General University Hospital in the municipality of Bayamo, Granma province, in the period of time from January 2018 until December 2022. The dependent variable was determined: infection associated with ischemic stroke and as independent variables the factors with possible influence on the development of infection associated with ischemic stroke. The means and standard deviations were determined, along with the minimum and maximum values of each distribution and absolute and relative frequencies were obtained. Results: the binary logistic regression model, adjusted by the forward method, identified that the factors with independent influence are the NIHSS score > 13 points (OR = 18.0; 95 % CI = 7.3 - 44.3; p= 0.000), neurodegenerative diseases (OR = 17.3; 95 % CI = 3.4 - 87.8; p= 0.001), dysphagia (OR = 6.2; 95% CI = 2.5 - 15 .3; p= 0.000) and atrial fibrillation (OR = 4.2; 95 % CI = 1.4 - 12.5; p= 0.008). Conclusions: the severity of ischemic stroke, the coexistence of neurodegenerative diseases and dysphagia constitute the main risk factors for infection associated with ischemic stroke in patients over 60 years of age.